Structural basis for selectivity of the isoquinoline sulfonamide family of protein kinase inhibitors. - Xu, R M (1996)
A large family of isoquinoline sulfonamide compounds inhibits protein kinases by competing with adenosine triphosphates(ATP), yet interferes little with the activity of other ATP-using enzymes such as ATPases and adenylate cyclases. One such compound, N-(2-aminoethyl)-5-chloroisoquinoline-8-sulfonamide (CK17), is selective for casein kinase-1 isolated from a variety of sources. Here we report the crystal structure of the catalytic domain of Schizosaccharomyces pombe casein kinase-1 complexed with CK17, refined to a crystallographic R-factor of 17.8% at 2.5 angstrom resolution. The structure provides new insights into the mechanism of the ATP-competing inhibition and the origin of their selectivity toward different protein kinases. Selectivity for protein kinases versus other enzymes is achieved by hydrophobic contacts and the hydrogen bond with isoquinoline ring. We propose that the hydrogen bond involving the ring nitrogen-2 atom of the isoquinoline must be preserved, but that the ring can flip depending on the chemical substituents at ring positions 5 and 8. Selectivity for individual members of the protein kinase family is achieved primarily by interactions with these substituents.